Outros quartos e outros despejos: uma colchagrafia de narrativas acerca do racismo ambiental a partir do sujeito-escola - Silva, Iago Gomes da (2024)
This thesis presents a narrative analysis of environmental racism as a structuring marker of the space-time relationships of young students from a public school in the inland of Bahia, which I characterize as a subject-school. A critical-theoretical reflection on the research topic was carried out, already surrounded by narrative experiences encountered throughout the field, also reflecting on them from the perspective of decolonial and post-critical education, which makes it possible for us to reach not only a counter-hegemonic position but an engaged one, in which the subjects become the very constructors of this research. To this end, it was used the methodological approach of Cartography, inspired by philosophers Gilles Deleuze and F?lix Guatarri, which therefore includes resources such as participant observation, conversation, and interventional research, characterizing a qualitative approach. As a methodological stimulus and characterization of the researcher and creator's action, the work "Quarto de Despejo: di?rio de uma favelada" by Carolina Maria de Jesus was used, which generated narrative possibilities for the creation of the cartographic clues that make up the "colchagrafia" produced at the end of this work. This research thus guides the identification of environmental racism as an emerging theme for educational research, in a conception that not only takes environmental education as a specific area but as a theme that is transversalized and supported by the adjective anti-racist and amplified by aesthetic-artistic approaches that expand narrative forms in the face of the environmental challenge of current times.